Reasons for discontinuation of tuberculosis treatment provided by BRAC - Mahmud, Shah Noor; Ali, Ahmed; Islam, Md. Nazrul; Karim, Fazlul (BRAC Research and Evaluation Division (RED), 2019)
To supplement the government tuberculosic; control programme, BRAC has initiated a communitybased tuberculosis programme in 10 thanas under the Women's Health and Development Programme (WHDP) (presently known as Reproductive Health and Disease Control - RHDC) since June 1992. BRAC is delivering services and following up the patients for all compliance. But, a recent study showed that the treatment completion rate achieved was up to 85% (1). Now the question arises: why the remaining 15% of the patients did not complete their treatment course? This study aimed to assess the reasons for discontinuation of treatment from BRAC's community-based TB control programme. The study was carried out in all10 WHDP thanas and dealt with the patients receiving only 12 months treatment regimen. The patients who enrolled and later discontinued treatment dwing June 1993 to May 1994 were selected for the study. Reasons for discontinuation of treatment were collected from progranune records, the patient or his/her relatives, Shastho Shebikas (SSs), Programme Organisers (POs), Area Managers (AMs) and Medical Officers (MOs) through indepth interviews during J\Ule and August 1994. A total of 1,538 patients were enrolled between JWte 1993 and May 1994. Of them, only 40 patients were found to have discontinued from BRAC treatment. Among these patients, 20 (50%) defaulted or dropped out, 5 (12.5%) were migrated and the rest 15 (37.5%) were referred to TB clinic or hospital for treatment.